The Psychological Status of General Population in Hubei Province During the COVID-19 Outbreak: A Cross-Sectional Survey Study - Chen, Guanmao; Gong, Jiaying; Qi, Zhangzhang; Zhong, Shuming; Su, Ting; Wang, Jurong; Fu, Siying; Huang, Li; Wang, Ying (Frontiers in Public Health, 2021)
Introduction: The current outbreak of the novel coronavirus disease 2019 (COVID-19), originating from Wuhan (Hubei, China), has rapidly spread across China and several other countries. During the outbreak of COVID-19, mental health of the general population in Hubei province may be affected. This study aimed to assess the psychological status and associated risk factors of the general population in Hubei province during the COVID-19 outbreak. Methods: A cross-sectional online survey was used to evaluate the symptoms of posttraumatic stress disorder (PTSD), depression, and anxiety, which were assessed by the Chinese version of the Impact of Event Scale—Revised, the Patient Health Questionnaire 9, and the seven-item Generalized Anxiety Disorder Scale, respectively. Coping style was assessed by the Simplified Coping Style Questionnaire. Multivariate logistic regression analysis was carried out to detect factors associated with mental health outcomes. Results: Among 9,225 participants, 44.5% rated symptoms of PTSD, and 17.9 and 12.7% suffered from moderate and severe symptoms of depression and anxiety, respectively. Individuals who were geographically located in Wuhan and familiar with someone who has COVID-19 had more severe symptoms of PTSD, depression, and anxiety, as well as a higher score in passive coping style (P < 0.05). Multivariate logistic regression analysis showed that people who were geographically located in Wuhan [odds ratio (OR) = 1.25, 95% confidence interval (CI) = 1.14–1.36, P < 0.001] were associated with severe symptoms of PTSD. Besides, individuals who were familiar with someone who had COVID-19 (OR = 2.33, 95% CI = 2.07–2.63, P < 0.001; OR = 1.90, 95% CI = 1.66–2.17, P < 0.001; OR = 2.06, 95% CI = 1.78–2.39, P < 0.001) and had a higher score in passive coping style (OR = 1.16, 95% CI = 1.14–1.17, P < 0.001; OR = 1.17, 95% CI = 1.15–1.19, P < 0.001; OR = 1.17, 95% CI = 1.15–1.19, P < 0.001) were associated with severe symptoms of PTSD, depression, and anxiety. Moreover, a higher score in active coping style (OR = 0.96, 95% CI = 0.95–0.97, P < 0.001; OR = 0.94, 95% CI = 0.93–0.94, P < 0.001; OR = 0.95, 95% CI = 0.94–0.96, P < 0.001) was associated with a lower risk of symptoms of PTSD, depression, and anxiety. Conclusions: During the midphase of COVID-19 outbreak, quite a few people have mental health problems; nearly half of the respondents rated symptoms of PTSD, and approximately one-fifth reported moderate to severe symptoms of anxiety and depression. Our findings may lead to better comprehend the psychological status of the general public and alleviate the public mental health crisis during the COVID-19 outbreak.